Impact of Eclecticism on Nigerian ESL learners’ communicative competence: A comparative study (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
This study adopted three practical teaching strategies intended to positively affect learners’ writing skill while neutralising negative factors affecting their writing competence.To achieve the study objective which aimed at the assessment of the best teaching strategy to enhance learners’ writing proficiency, a comparative study of three teaching methods(namely communicative, eclectic and task-based methods) was used over a-6-week period as treatment on three experimental groups A, B, C respectively and a control group (D) was taught using conventional method. A pre-test was administered on two hundred (200) freshmen/subjects purposively selected from different Departments at the Federal University of Technology, Owerri (FUTO). A post-test was used to ascertain the outcome of the six weeks period of treatment on their essay writing. Results varied according to groups but, most importantly, Group B showed very significant improvement and control group D showed no significant improvement at all in the post-test assessment while groups A and C’s writing ability improved just marginally at best post-test. Our findings suggest the need to pay attention to eclectic teaching technique as a crucial element in enhancing writing proficiency among learners. The implications and limitations of this research in addition to guidelines for future research are discussed.